Evaluación de susceptibilidad de fenómenos de remoción en masa y uso de sistemas de información geográfica (2016)
The evaluation and zoning of the susceptibility to Mass Wasting Phenomena (MWP) in Colombia is becoming more and more important due to the human growth that major cities have experienced, leading to the use of areas not considered suitable for human settlement. Among the natural processes that can occur in an area, MWPs have a higher chance of occurrence due to their direct relationship with changes in subsoil humidity, topographical variation, precipitation, geological formations, soil use and anthropic activities. As shown by the Administrative Department of National Statistics (DANE), between 1993 and 2005 Tunja went from having a population of 107,807 to one of 152,419 with an increase of 1.4%. Due to this, areas are beginning to be used which were previously used for activities of agriculture, shepherding, reforestation and that exhibit erosion. In this study the Ramírez and Gonzales (1989) methodology and the Omar Jiménez (2009) methodological proposal were used, integrated with the geographical information systems SIG for data processing and plan presentation. The necessary information in each methodology, was obtained by dividing the study area into a net with square components with 50m sides; this size is sufficient for the considered level of detail. Each cell is characterized with all variables (geology, erosion, etc.), so that a matrix is obtained with dimensions Ma x Mb, where Ma is the number of cells (3623) and Mb is the number of studied variables.